Cognition and emotion : exploration on consumers response to advertisement and brand - Hafizah Omar Zaki; Yusniza Kamarulzaman; Mozard Mohtar (Penerbit Universiti Kebangsaan Malaysia, 2021)
Cognition and emotion are known to be drivers of information and message processing, leading to attitude formation. This research hypothesises that emotion, specifically intense positive mood, would elicit better ad and brand evaluations. This paper examined the role of the Associative Network Theory of Memory and Emotion (ANTME) within the framework of the Elaboration Likelihood Model (ELM). Adopting experimental method, the results confirmed most of our hypotheses. In four experimental studies via the purposive sampling method, undergraduate students were invited to volunteer in the experiments (N = 389). Study 1 (n = 60) established ELM as a framework within the sampling frame. The results indicate that individuals' difference in the need for cognition (NFC) evaluate both ad and brand differently. In study 2 (n = 131), despite having elicited positive and negative mood valence, none of the moods successfully boost the evaluations of ads and brands for either low or high NFC individuals. In study 3 (n = 129), the results indicate that only intense positive mood successfully garner favourable brand evaluation. Lastly, in study 4 (n = 69), the results reveal that prior exposure to a humourous stimulus (i.e., comic strip) affects ad evaluation only. This research offers some theoretical contributions to the establishment of cognition as drivers to information processing and ELM attitude formation; and insights into consumers' cognitive-emotional attempts in response to advertising and brands which may become an input for advertisers, brand builders and marketing firms to design more innovative and impactful advertising campaigns for a sustainable IMC. Further, it could assist policymakers and regulators in improving the existing advertising guidelines and policies in Malaysia.